2016
DOI: 10.1155/2016/2867097
|View full text |Cite
|
Sign up to set email alerts
|

Does Acellular Dermal Matrix Thickness Affect Complication Rate in Tissue Expander Based Breast Reconstruction?

Abstract: Background. While the benefits of using acellular dermal matrices (ADMs) in breast reconstruction are well described, their use has been associated with additional complications. The purpose of this study was to determine if ADM thickness affects complications in breast reconstruction. Methods. A retrospective chart review was performed including all tissue expander based breast reconstructions with AlloDerm (LifeCell, Branchburg, NJ) over 4 years. We evaluated preoperative characteristics and assessed postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…While some authors advocate the use of ADM and propose a better perfusion of the skin flap after mastectomy [16], several authors remark that the ADM needs profound perfusion for integration. This might not be the case in critically per- (thickness > 1.2 mm) ADM are used [22]. As the thickness of the ADM increases, perfusion and ingrowth of repopulating cells gets more difficult and renders these ADM more prone to failure of integration.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors advocate the use of ADM and propose a better perfusion of the skin flap after mastectomy [16], several authors remark that the ADM needs profound perfusion for integration. This might not be the case in critically per- (thickness > 1.2 mm) ADM are used [22]. As the thickness of the ADM increases, perfusion and ingrowth of repopulating cells gets more difficult and renders these ADM more prone to failure of integration.…”
Section: Discussionmentioning
confidence: 99%
“…Common complications to the use of ADM include infection, wound dehiscence, necrosis, seroma, haematoma, capsular contracture, extrusion, loss of implant and reconstruction failure. Thick ADMs appear to have an overall higher rate of complications compared to thinner ADMs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pliable version of Strattice is recommended for breast reconstruction. Compared to other ADMs, Strattice appears to be integrated slower, perhaps due to its greater thickness [ 11 ]. A large-animal study [ 12 ] found in that ADMs typically obtain early angiogenesis at 4 weeks after implantation and flow at 12 weeks after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Seroma is a relatively frequent postoperative complication that is associated with breast tissue expander (TE) insertion. A small amount of seroma is usually spontaneously absorbed by the surrounding tissue; however, the prolonged presence of seroma can cause infection and purulency 1 , 2 ; thus, the removal of the TE cannot be avoided in some cases. For this reason, obvious fluid collection around a TE should be drained as soon as possible.…”
Section: Introductionmentioning
confidence: 99%